Evaluating evidence of childhood abuse as a function of expert testimony, judge's instructions and sentence recommendation - Platania, Judith (Applied psychology in criminal justice, 2014)
In the current study we examined how jurors utilize evidence of childhood abuse as afunction of expert testimony and sentence recommendation. We also varied the specificityof instructional language in the context of mitigating circumstances. We predicted jurorswho impose a life sentence would rate evidence of childhood abuse as significantly moreimportant in determining sentence compared to jurors who impose the death penalty.Furthermore, we expected this effect to be moderated by expert testimony. Testimony ofchildhood abuse increased importance ratings of non-statutory mitigating circumstances.This effect was more evident for jurors who imposed a life sentence compared to thosewho imposed the death penalty. In addition, specific instructional language influenced howjurors considered circumstances related to the defendant's life.